Hollard : the office move - Beswick, Claire; Viedge, Conrad ([London] : SAGE, 2016)
By April 2009, Hollard Insurance had been in Arcadia, its new building, for a little over three years. A key motive behind the move had been to draw all Hollard employees together, so as to sustain and reinforce a common culture and facilitate communication across business units. Now, Hollard's CEO, Nic Kohler, had a few things to consider: had the new building had an impact on Hollard's culture, and on balance; had this been positive; and should he now move the company's call centres to a smaller town, where competition for talent would be less intense?
Originally Published in: Beswick, C., & Viedge, C. (2009). Hollard: The Office Move. WBS-2009-7. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Hollard Insurance; Corporate culture -- Case studies; Personnel management -- Case studies; Leadership -- Case studies